Factor Related To The Readiness Of Young Women To Face Menarche At SDN 03 Cikodom Gunung Sindur Bogor - Marisa Marcelina Limbong; Nurannisa Fitria Aprianti; Ayu Rimanda; D. Mustamu Qamal Pa’ni (UMBanjarmasin, 2025)
Puberty in adolescent girls is marked by the occurrence of menstruation for the first time. The factors of readiness to face menarche are age, knowledge, availability of information, the role of mothers and peer support. The study aims to find out the factors related to the readiness of adolescent girls to face menarche at SDN 03 Cikodom Gunung Sindur Bogor. This study employs a quantitative research method with a crossectional study approach. The research will be carried out in December 2023 - February 2024. The population and sample were all female students in grades IV and V totaling 60 people with a total sampling technique. Analysis used chi square Test. Results: there was a relationship between age p = 0.019, knowledge p = 0.011, availability of information p = 0.000, maternal role p = 0.000 and peer support p = 0.019 with the readiness of adolescent girls in facing menarche. It is hoped that health workers can provide information about menstruation, and efforts to deal with menarche so that they can prepare earlier in facing the menarche period